Expression and associations of TRAF1, BMI-1, ALDH1, and Lin28B in oral squamous cell carcinoma. Issue 4 (April 2017) - Wu, Tian-Fu; Li, Yi-Cun; Ma, Si-Rui; Bing-Liu,; Zhang, Wen-Feng; Sun, Zhi-Jun
Tumor necrosis factor receptor–associated factor 1, an adaptor protein of tumor necrosis factor 2, is involved in classical nuclear factor (NF)-κB activation and lymphocyte recruitment. However, less is known about the expression and association of tumor necrosis factor receptor–associated factor 1 with cancer stem cell markers in oral squamous cell carcinoma. This study aimed to investigate the expression of tumor necrosis factor receptor–associated factor 1 and stem cell characteristic markers (lin28 homolog B, B cell-specific Moloney murine leukemia virus integration site 1, and aldehyde dehydrogenase 1) in oral squamous cell carcinoma and analyze their relations. Paraffin-embedded tissues of 78 oral squamous cell carcinomas, 39 normal oral mucosa, and 12 oral dysplasia tissues were employed in tissue microarrays, and the expression of tumor necrosis factor receptor–associated factor 1, B cell-specific Moloney murine leukemia virus integration site 1, aldehyde dehydrogenase 1, and lin28 homolog B was measured by immunohistostaining and digital pathological analysis. The expression of tumor necrosis factor receptor–associated factor 1 was higher in the oral squamous cell carcinoma group as compared with the expression in the oral mucosa (p < 0.01) and oral dysplasia (p < 0.001) groups. In addition, the expression of tumor necrosis factor receptor–associated factor 1 was associated with those of B cell-specific Moloney murine leukemia virus integration site 1, aldehyde dehydrogenase 1, and lin28 homolog B (p = 0.032, r 2 = 0.109; p < 0.0001, r 2 = 0.64; and p < 0.001, r 2 = 0.16) in oral squamous cell carcinoma. The patient survival rate was lower in the highly expressed tumor necrosis factor receptor–associated factor 1 group, although the difference was not significant. The clustering analysis showed that tumor necrosis factor receptor–associated factor 1 was most related to aldehyde dehydrogenase 1. These findings suggest that tumor necrosis factor receptor–associated factor 1 has potential direct/indirect regulations with the cancer stem cell markers in oral squamous cell carcinoma, which may help in further analysis of the cancer stem cell characteristics.